Chronique prétendue de l’événement extraordinaire : l’incipit de la deuxième partie de La Araucana - Florence d’Artois (Etudes Epistémè)
This article focuses on the incipit of the second part of La Araucana by Alonso de Ercilla. The incipit relates a triple contingent event (the apparition of a comet, an earthquake, a lightning strike) concomitant with the arrival of captain Hurtado de Mendoza into Chile. By comparing this episode from Ercilla’s work with the chronicles which refer to the captain’s arrival, the article shows how the epic in fact makes up the three meteorological wonders and claims them to be true in order to elaborate a political meaning.